2018
DOI: 10.1128/aac.00402-18
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Real-World Study of the Impact of an Antifungal Stewardship Program in a Tertiary Respiratory-Medicine Setting

Abstract: There has been an increase in fungal infections in patients with chronic lung disease over the past decades, which is associated with rapidly increasing costs to health care systems. An antifungal stewardship team was introduced to a tertiary cardiopulmonary hospital, consisting of a medical mycologist and pharmacy support providing weekly stewardship ward rounds, twice-monthly multidisciplinary team meetings, and a dedicated weekly outpatient clinic. A database was set up to record the activity of the steward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Over the previous 10 years, there has been an increase in studies assessing the impact of antifungal stewardship (AFS) interventions, demonstrating improvements in the quality of antifungal prescribing, [15][16][17][18] reduction in the consumption of high-cost antifungals, 19 and improvements in the application of fungal diagnostics 17 and therapeutic drug monitoring (TDM) of antifungals. 20 Pharmacists are key members of antimicrobial stewardship (AMS) teams globally and have shown that they can lead AMS programs. 21 Despite a recent focus on AFS, 22 the role of the pharmacist in AFS has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Over the previous 10 years, there has been an increase in studies assessing the impact of antifungal stewardship (AFS) interventions, demonstrating improvements in the quality of antifungal prescribing, [15][16][17][18] reduction in the consumption of high-cost antifungals, 19 and improvements in the application of fungal diagnostics 17 and therapeutic drug monitoring (TDM) of antifungals. 20 Pharmacists are key members of antimicrobial stewardship (AMS) teams globally and have shown that they can lead AMS programs. 21 Despite a recent focus on AFS, 22 the role of the pharmacist in AFS has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are significant limitations in the evidence on antifungal stewardship application in a chronic respiratory care setting [22,23,24]. Two of the included studies (Nwanko et al and Browne et al) are classified as low-quality evidence according to GRADE classification [9,17]. The prospective and retrospective studies highlighting antifungal stewardship in respiratory care settings may contain bias given the small sample size utilized in both studies with imprecisions due to a confidence interval of less than 95% in the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant fungal infection studied in the eligible articles with inclusion of patients with underlying chronic respiratory disease was Candida species with 25 out of 29 articles focussing on invasive fungal disease infection (IFI). Although fourteen studies included sample populations consisting of patients with chronic respiratory illnesses, only two studies (Nwanko et al and Browne et al) had a focus specifically on chronic respiratory fungal infections and pulmonary aspergillosis, indicating a gap in existing knowledge/evidence base in the use of antifungal stewardship in this field [9,17]. Although focussed in an invasive fungal infection setting, the implementation of antifungal stewardship was shown to be an effective intervention in a number of the included studies, with some (n = 3) having a moderate GRADE quality of evidence.…”
Section: • Disease Area Of Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal stewardship programs (ASPs) have been proposed as an opportunity to optimize antifungal use [ 3 , 4 , 5 , 6 , 7 ]. Most of the ASPs are exclusively based on restrictive prescription strategies or pharmacy alerts, and few of them are based on bedside interventions [ 8 , 9 , 10 , 11 , 12 ]. While different models of ASPs have been designed for intensive care units (ICUs) and onco-hematology units [ 13 , 14 ], not much attention has been paid to SOT and oncologic units.…”
Section: Introductionmentioning
confidence: 99%